Aquatic pollutants are associated with reproductive alterations and genotoxicity in estuarine fish (Sciades herzbergii - Bloch, 1794) from the Amazon Equatorial Coast - K. S. Noleto; D. C. S. Mendes; I. F. S. Carvalho; D. L. S. Ribeiro; D. M. S. Santos; A. P. M. Ferreira; A. L. B. Marques; R. N. F. Carvalho Neta; L. Tchaicka; J. R. S. Torres Júnior (Brazilian Journal of Biology, 2022)
Abstract Estuaries are constantly subject to continuous environmental impacts of human activities, such as fisheries, port or industry, and domestic sewage, with fish being one of the most affected aquatic animals, reflecting the impacts directly on their bodies. Thus, the aim of this study was to carry out the biomonitoring of an estuary located on the Amazonian Equatorial Coast through analysis of PAHs (Polycyclic Aromatic Hydrocarbons) in the water, in addition to trace metals, histopathological alterations and analysis of erythrocyte micronuclei in Sciades herzbergii. S. herzbergii was used as a model species, due to its estuarine-resident behavior. Gonad and gill samples were subjected to histopathological evaluations. The quantification of trace metals was performed in samples of skeletal muscles of the animals collected, where concentrations of Lead (Pb), Copper (Cu), Zinc (Zn), Cadmium (Cd), Magnesium (Mg), Iron (Fe) and Aluminum (Al) were found. Except for Cadmium (Cd), all the concentrations were above the recommended limits. The PAHs analysis revealed the presence of Naphthalene and Acenaphthene in the water samples Histopathological and genotoxic analyses revealed of lesions in 100% of the study specimens. Thus, the histological and genotoxic alterations found in 100% of S. herzbergii specimens captured in São José Bay-MA are potentially associated with PAH concentrations present in the water. These results are potentially associated with the presence of PAH and trace metals, both in water and in animal tissues, inferring a general scenario of environmental contamination which directly implies a risk to the health and survival of the local biota. This study shows the relevance of continuous biomonitoring of estuarine ecosystems, in order to guide authorities regarding sewage management and ensure the evolutionary development of estuarine species, especially fishes of importance in the local cuisine, therefore related to human food security.